Construction of Inheritance Distribution Based on Gender Equality in Thematic Tafsir Studies - Tarmizi, Tarmizi; Abubakar, Achmad; Basri, Halimah; Febrian, Rifki; Rif’ah, Muh. Azka Fazaka (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2024)
Gender equality in inheritance is an issue that is often debated today. One of the controversial verses is verse 11 of surah al-Nisa' which regulates that the men's portion is equal to two women's parts. This study aims to examine the verses of the Qur'an regarding gender equality in inheritance through thematic studies and spark a shift in the concept of inheritance which demands equal parts through the interpretation of the meaning of verse 11 surah al-Nisa'. This research is literature research with descriptive qualitative type through thematic tafsir approach and syar'i approach. This research found that the verses of the Qur'an regarding gender equality in inheritance based on thematic studies produced the theme, namely the verses about men and women being equally entitled to inherit and the share of men and women heirs, as well as the share of men and women. Through thematic studies, the concept of inheritance based on gender equality can be explained more comprehensively. The concept of inheritance in verse 11 of surah al-NisÄ' has gradually shifted in meaning from section 2:1 to become an equal part marked by the birth of the concept of bilateral inheritance which fully supports gender equality in inheritance. It's just that it is still possible for disputes to occur so fiqh mawÄris becomes a solution. So it is recommended that before dividing the inheritance with the principle of gender equality, it must first be divided based on the provisions of the mawÄris fiqh and then an agreement can be made so that the rights of the heirs are considered.